2020
DOI: 10.21203/rs.3.rs-28463/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Anemia and associated factors among adolescent girls and boys at 10-14 years in rural western China

Abstract: Background: Evidence on the anemia and associated factors among young adolescent girls and boys in rural western China is limited.Methods: We used data from a follow-up study of adolescents (10-14 years) born to women who participated in a randomized trial of antenatal micronutrient supplementation in western China. Anemia was defined by World Health Organization standards. Logistic regression was used to examine the associated factors with anemia.Results: The overall prevalence of anemia was 11.7% (178/1517).… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
2
2
1
2
Order By: Relevance
“…The odds of having anaemia among adolescent girls who lived in high-altitude areas (ie, altitudes greater than 2000 m above sea level) were higher than their counterparts. This result is in agreement with previous studies done in India,42 sub-Saharan Africa,43 China36 and Ethiopia 31 39 44. This is because in areas with high altitudes agricultural products were relatively low, which could increase the risk of being anaemic.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The odds of having anaemia among adolescent girls who lived in high-altitude areas (ie, altitudes greater than 2000 m above sea level) were higher than their counterparts. This result is in agreement with previous studies done in India,42 sub-Saharan Africa,43 China36 and Ethiopia 31 39 44. This is because in areas with high altitudes agricultural products were relatively low, which could increase the risk of being anaemic.…”
Section: Discussionsupporting
confidence: 92%
“…However, the finding of this study was higher than the studies conducted in western China (14.4%)36 and Bahir-Dar, Ethiopia (11.1%). The possible explanation might be related to the economic status of the population, education access, youth-friendly services, and water and sanitation services were good in China 37.…”
Section: Discussioncontrasting
confidence: 86%
“…Although there is no definitive explanation for this phenomena, it may be that the hormonal effects on erythropoietin activity and the higher pre- and postnatal growth rate may play a role in the increased susceptibility of male children to anemia [ 28 , 29 ]. Conversely, other studies have demonstrated girls to have higher rates of anemia than boys [ 31 , 32 ]. Reverse causation may partly explain the relationship between anemia in boys and girls.…”
Section: Discussionmentioning
confidence: 93%
“…Besides lack of knowledge, low financial status, female gender and limited usage of eggs, flesh food and milk products as well consumption of meal 1-2 times /day may increase the risk of development of anemia. 22 One of the study reported that Indian girls in their adolescent age have a habit to use food rich in vitamin with less amounts of protein in comparison with boys. 23 Levels of fasting blood sugar and insulin resistance were increased in cases as compared to controls.…”
Section: Discussionmentioning
confidence: 99%